“Mães na luta contra violência obstétrica”: a dor do parto transformada em movimento social - Rocha, Bruna Fani Duarte (2021)
This study deals with the formation process of a social movement built by women who recognize themselves as victims of obstetric violence. The research includes the relations between activism and emotions in the formation of the group “Mothers in the fight against obstetric violence”. The research design, predominantly qualitative with ethnographic method, was carried out with the use of childbirth reports on digital media, participant observation and document records related to the group mobilizations and public manifestations in the city of Santa Maria. This work provided a debate about childbirth and the different social actors involved in this event as well as an in-depth knowledge about the operating logic of this group, its formation process, and how emotions are engaged in political actions, in the conversion to activism and its connections on and off-line. It was observed that with different emotional configurations, mothers compose “emotional communities” where they exchange experiences and narratives about a place of recognition of their own bodies. The acknowledge of pain, anger, anguish and violation is what legitimizes and embodies this sensitivity in the condition of being a woman, of being a mother, and impacts in the conversion to activism as an expression of this suffering.